PREVALENSI SINDROMA METABOLIK PADA POPULASI PENDUDUK BALI, INDONESIA - Dwipayana, M Pande; Suastika, K; Saraswati, IMR; Gotera, W; Budhiarta, AAG; -, Sutanegara; Gunadi, IGN; Badjra Nadha, K; Wita, W; Rina, K; Santoso, A; Kajiwara, N; Taniguchi, H (journal of internal medicine, 2011)
An epidemiological study on metabolic syndrome (MS) in seven villages population of Bali (6 villages and 1 suburban),Indonesia have been conducted. One thousand eight hundred fourty (age, 13